Perdida de juegos tradicionales limita el desarrollo del turismo cultural en el cantón Babahoyo - Pinto Jiménez, Génesis Lilibeth (2019)
For decades, tourism has undergone a continuous transformation that has allowed it to grow faster and deeply diversify, becoming a key factor in socioeconomic progress. This study has sought the valorization of cultural wealth through traditional games, determining their impact on cultural tourism with the purpose of increasing their development and strengthening the conservation of customs, the same that can be transmitted from one generation to other. This case study directly observed the problem that the Canton is experiencing in the absence of the tourist promotion of its traditional popular games and the acceptance that these activities have on the part of its locals and visitors, the surveys and interviews reaffirm the research to proceed to give our point of view in the conclusions and recommendations in order to find tentative solutions that fit the topic under discussion